Factors Associated With Interprofessional Collaboration for Handling Stunting In Children - Nursalam . (Journal of Global Pharma Technology, 2019)
Objective: An estimated in every 4 (25%) infants and toddlers were stunted in Surabaya. With slow progress in stunting reduction in this many regions is not due to insufficient diet alone, it needs interprofessional collaboration (IPC) which will improve the performance of health workers in the management of stunting. The aimed of this study is to understand the knowledge, attitude, self-efficacy, collaboration, communication about interprofessional collaboration to handle children aged < 5 years were stunted. Methods: The research used a cross-sectional study. The population in this study was 128 health workers. Samples were taken by simple random sampling. Independent variables were knowledge, attitude, self-efficacy, collaboration communication. The dependent variable was interprofessional collaboration. The instrument used a questionnaire. Data were analyzed by using correlation and logistic regression with a significance level of p <0.05. Results: The focus of this study is to understand the knowledge, attitude self-efficacy, collaboration communication in interprofessional collaboration as a way to handle stunting aged < 5 years; for self-efficacy p=0,027. A health worker who had good knowledge, attitude self-efficacy, collaboration communication, impacted and improve interprofessional collaboration as a prevention eﬀort against stunting. Conclusion: From this study, we can conclude that the knowledge, attitude, self-efficacy, collaboration communication improve interprofessional collaboration in handling stunting in children under five. The better knowledge, attitude and belief about interprofessional collaboration, the better the implementation of interprofessional collaboration.Keywords: Factor personal, Interprofessional collaboration, Stunting, Children.